SENIOR HIGH SCHOOL STUDENTS’ DIFFICULTIES IN READING COMPREHENSION - Zuhra Zuhra (Universitas Syiah Kuala, 2015)
This study aims at finding out the most difficult types of reading comprehension questions faced by students in reading tests and why they face these difficulties in the national examinations. Purposive sampling was used and the sample selected was 24 12th grade students of senior high school Lhokseumawe. The instruments used were a test, a questionnaire, and an interview guide. Based on the results from the test, the researcher found that the most difficult type of reading comprehension question faced by the students was an inference question, and this type of question was also classified into the difficult questions based on the index of difficulty formula. After analyzing the data from the questionnaire, it was found that most of students failed to answer the inference questions correctly because they did not fully understand what was being asked and because of weakness in understanding the reading comprehension questions. From the interview, the researcher found that the students had an inadequate knowledge of vocabulary and sentence structure but they lacked knowledge about different types of reading comprehension questions. It can be concluded that there were some factors that caused difficulties for the students in answering these tests. First, the students did not comprehend the questions asked due to their weaknesses in differentiating between the natures of different types of reading comprehension questions. Their difficulties were also influenced by their weaknesses in mastering a wide range of vocabulary and sentence structures.